Prospective validation of prognostic and diagnostic syncope scores in the emergency department. (15th October 2018) - du Fay de Lavallaz, Jeanne; Badertscher, Patrick; Nestelberger, Thomas; Isenrich, Rahel; Miró, Òscar; Salgado, Emilio; Geigy, Nicolas; Christ, Michael; Cullen, Louise; Than, Martin; Martin-Sanchez, F. Javier; Bustamante Mandrión, José; et al.
Abstract: Background: Various scores have been derived for the assessment of syncope patients in the emergency department (ED) but stay inconsistently validated. We aim to compare their performance to the one of a common, easy-to-use CHADS2 score. Methods: We prospectively enrolled patients ≥ 40 years old presenting with syncope to the ED in a multicenter study. Early clinical judgment (ECJ) of the treating ED-physician regarding the probability of cardiac syncope was quantified. Two independent physicians adjudicated the final diagnosis after 1-year follow-up. Major cardiovascular events (MACE) and death were recorded during 2 years of follow-up. Nine scores were compared by their area under the receiver-operator characteristics curve (AUC) for death, MACE or the diagnosis of cardiac syncope. Results: 1490 patients were available for score validation. The CHADS2 -score presented a higher or equally high accuracy for death in the long- and short-term follow-up than other syncope-specific risk scores. This score also performed well for the prediction of MACE in the long- and short-term evaluation and stratified patients with accuracy comparative to OESIL, one of the best performing syncope-specific risk score. All scores performed poorly for diagnosing cardiac syncope when compared to the ECJ. Conclusions: The CHADS2 -score performed comparably to more complicated syncope-specific risk scores in the prediction of death and MACE in ED syncope patients. While better tools incorporating biochemical and electrocardiographic markers are needed, this study suggests that the CHADS2 -score is currently a good option to stratify risk in syncope patients in the ED. Trial registration:NCT01548352 Highlights: Syncope scores perform poorly to predict cardiac origin or major adverse events (MACE) in the Emergency Department (ED). A simple CHADS2 score performs comparably to syncope-specific risk scores to predict death or MACE. Better diagnostic and risk-stratification tools including biochemical and electrocardiographic markers are needed.